(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The court costs are included in the costs of proceedings and imply all fees and expenses. It is of principal rule that in civil cases the litigation parties bear the costs that arise in court proceedings. Exemption from this principle are all legally sanctioned court fees before the proceedings are initiated or in their course at the request of an applicant, as well as in the case-finishing judgment in a given instance. The court fee exemption allows anyone to exercise their right of access to judiciary, but a detailed examination of the requirements for obtaining an exemption from court costs leads to the conclusion that it is only exceptionally applicable.